Change Rippling through Our Waters and Culture. (1st June 2020) - Martin, Christine; Doyle, John; LaFrance, JoRee; Lefthand, Myra J.; Young, Sara L.; Three Irons, Emery; Eggers, Margaret J.
Abstract: It is well established that climate change is already causing a wide variety of human health impacts in the United States and globally, and that for many reasons Native Americans are particularly vulnerable. Tribal water security is particularly threatened; the ways in which climate changes are damaging community health and well‐being through impacts on water resources have been addressed more thoroughly for Tribes in coastal, arid, and sub‐arctic/arctic regions of the United States. In this article, Crow Tribal members from the Northern Plains describe the impacts of climate and environmental change on local water resources and ecosystems, and thereby on Tribal community health and well‐being. Formal, qualitative research methodology was employed drawing on interviews with 26 Crow Tribal Elders. Multiple determinants of health are addressed, including cultural, social, economic, and environmental factors. The sense of environmental‐cultural‐health loss and despair at the inability to address the root causes of climate change are widespread. Yet the co‐authors and many other Tribal members are actively prioritizing, addressing, and coping with some of the local impacts of these changes, and are carrying on Apsáalooke [Crow] lifeways and values.